Academic Writing Workshop at One Junior High School in Merangin - Mukhlash Abrar; Nunung Fajaryani; Masbirorotni Masbirorotni; Habizar Habizar; Failasofah Failasofah (Jurnal Pengabdian Pada Masyarakat, 2022)
The purposes of this community service program were to motivate the teachers to publish and to share our experiences in academic writing, especially writing academic journal article(s). The participants of this workshop were 51 teachers in one of junior high schools (SMP) in Merangin. The workshop was done synchronously and divided into several sessions, including material presentation (concept of academic writing, steps in writing the paper academically, and component of academic writing especially journal article); question and answer; practice (analyzing the paper and formulating the problems); and feedback survey sessions. Based on the result of this program, it is recommended to have similar programs to motivate SMP teachers publish their articles.